Tree diseases and wood deterioration problems in Peninsular Malaysia - Lee, Su See (1985)
Disease outbreaks are seldom encountered or reported in natural forests. However, potentially serious disease problems are beginning to surface in plantations of fast-growing exotics, such as Acacia mangium and Eucalyptus camaldulensis. Diseases affecting these and other exotic species are discussed under separate sections on root, stem and foliage diseases. Wood deterioration and decay are mainly due to white rots and stain fungi. Some of the more important wood destroying fungi and the substrates on which they are commonly encountered are listed. Our knowledge of tree diseases and wood deterioration problems is very incomplete and more detailed and coordinated studies are needed, especially with the rapid development of forest plantations of exotic species.